Cephradine Penetration into Cerebrospinal Fluid and Effects of Its Administration into the Cerebral Ventricles of Cats - Harik, Sami I. (1977)
In cats that had high, sustained serum concentrations of cephradine, penetration of the drug into the cerebrospinal fluid (CSF) was poor. Serum cephradine levels were, on the average, 100-fold higher than the CSF levels. On the other hand, the direct injection of cephradine into the lateral cerebral ventricles of cats yielded high CSF cephradine concentrations without evidence of central nervous system toxicity.